Liability for damages of a board member of a housing community - Sikorska-Lewandowska, Aleksandra (Studia Iuridica Toruniensia, 2020)
The provisions of the Act of Ownership of Premises do not contain any special regulation regarding the liability for damages of board members of a housing community. In this situation, the general provisions of the Civil Code, that is the provisions concerning liability in tort and contractual liability, apply to the liability of a member of the management board for damage caused to the community. The provisions of the Code of Commercial Companies and Partnerships, and the provisions of Cooperative Law contain a separate regulation on the principles of liability of members of the management board of companies and cooperatives for damage caused in connection with the exercise of this role, which facilitates the laying of a claim for damages against a member of the management board.